2013
DOI: 10.1074/jbc.m112.428359
|View full text |Cite
|
Sign up to set email alerts
|

Dual Mechanism of Integrin αIIbβ3 Closure in Procoagulant Platelets

Abstract: Background: Inactivation of integrin ␣ IIb ␤ 3 reverses platelet aggregate formation upon coagulation. Results and conclusion: Platelets from patient (Scott) and mouse (Capn1 Ϫ/Ϫ and Ppif Ϫ/Ϫ ) blood reveal a dual mechanism of ␣ IIb ␤ 3 inactivation: by calpain-2 cleavage of integrin-associated proteins and by cyclophilin D/TMEM16F-dependent phospholipid scrambling. Significance: These data provide novel insight into the switch mechanisms from aggregating to procoagulant platelets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
157
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 104 publications
(178 citation statements)
references
References 42 publications
18
157
2
1
Order By: Relevance
“…The same holds for the Ca 2+ -dependent protease, calpain-1 (51k), which cleaves many cytoskeletal components and controls integrin closure in procoagulant platelets. 164 Another remarkable fact is that 2 of the highly expressed signaling proteins play a role in PKA-dependent inhibition of platelets, that is, the adenylyl cyclase-associated protein CAP1 (42k) and VASP, which is the major substrate of this cAMP-dependent protein kinase. 165 Although earlier data with mice indicated that the prostacyclin receptor (a key cAMPelevating receptor on platelets) is not required for normal hemostasis, 166 the abundance of these proteins supports a quantitatively important role of cAMP signaling in the control of platelet functions (see also above).…”
Section: What Can Quantitative Proteomics Tell Us About Platelet Biolmentioning
confidence: 99%
“…The same holds for the Ca 2+ -dependent protease, calpain-1 (51k), which cleaves many cytoskeletal components and controls integrin closure in procoagulant platelets. 164 Another remarkable fact is that 2 of the highly expressed signaling proteins play a role in PKA-dependent inhibition of platelets, that is, the adenylyl cyclase-associated protein CAP1 (42k) and VASP, which is the major substrate of this cAMP-dependent protein kinase. 165 Although earlier data with mice indicated that the prostacyclin receptor (a key cAMPelevating receptor on platelets) is not required for normal hemostasis, 166 the abundance of these proteins supports a quantitatively important role of cAMP signaling in the control of platelet functions (see also above).…”
Section: What Can Quantitative Proteomics Tell Us About Platelet Biolmentioning
confidence: 99%
“…After staining for 5 min, samples were analyzed with a FACScan flow cytometer (BD Accuri Cytometer). 6 In a separate set of experiments, reconstituted PRP was activated with tissue factor (2 pM) and CaCl 2 (16.7 mM) in the presence of GPRP (2 mM) at 37°C, after which samples were taken for fluorescent labeling. Analysis was by flow cytometry as described above.…”
Section: Flow Cytometric Platelet Analysesmentioning
confidence: 99%
“…1,2 In a growing thrombus, aggregated and procoagulant platelets form two distinct populations, 3,4 which is at least partly explained by the high Ca 2+ response required for PS exposure and coagulation factor binding, and by the calpain-dependent closure of active α IIb b 3 integrins after PS exposure, thus antagonizing inclusion of procoagulant platelets into a platelet aggregate. 5,6 However, another platelet population has also been identified, usually referred to as coated platelets, 7 which may partly overlap with the two other platelet populations described above. 3 In the initial paper, Dale et al describe COAT platelets (later renamed as coated platelets) as a population of platelets arising after combined stimulation with collagen and thrombin, which bind α-granule proteins, including factor V, fibrinogen, von Willebrand factor, thrombospondin, fibronectin and α 2 -antiplasmin, in a transglutaminase-dependent way via the formation of covalent serotonin conjugations.…”
mentioning
confidence: 99%
“…In agreement with our previous studies,13 almost all resting and T+C‐ stimulated PS− platelets had intact inner mitochondrial membrane potential, while the majority of PS+ platelets had depolarized mitochondria. PAC1 binding was decreased in PS+ platelets compared with T+C (PS−) platelets, confirming that integrin αIIbβ3 is in a resting conformation on procoagulant platelets, and differentiating this procoagulant platelet subpopulation from pro‐aggregatory platelets 18, 23…”
Section: Discussionmentioning
confidence: 75%
“…Flow cytometric analysis of PS‐exposing platelets in suspension using fluorescently‐labeled annexin A5, first described over two decades ago,20 has become widely used in studies of procoagulant platelets and platelet‐derived extracellular vesicles (EVs) 4, 21, 22, 23, 24, 25. A limitation of traditional flow cytometry is the lack of images of individual analyzed cells.…”
Section: Introductionmentioning
confidence: 99%